Human coagulation factor Va is a cofactor for the activation of protein C. - Salem, H H (1983)
During blood clotting in vitro, protein C is converted in part to protein Ca, Protein Ca, in turn, inactivates factor Va. This is evidenced by the rapid inactivation of factor Va coagulant activity after clot formation which is associated with the cleavage of the Mr 110,000 peptide of factor Va. When exogenous factor Va is added to serum, it is inactivated only after a lag of 10-20 min. Using purified coagulation factors in the presence of EDTA, we demonstrated that factor Va enhances the rate of protein C activation by thrombin by 50-fold. The Km for factor Va in the reaction is 14 nM, 100 times higher than its Km for accelerating platelet surface prothrombin activation by factor Xa. By this mechanism, factor Va can act as a procoagulant as well as limit dissemination of the coagulation process through the activation of protein C and the subsequent inactivation of both factor Va and factor VIIIa.